Jewish memory and the cosmopolitan order : Hannah Arendt and the Jewish condition. - Sznaider, Natan (Polity Press, 2011)
Natan Sznaider offers a highly original account of Jewish memory and politics before and after the Holocaust. It seeks to recover an aspect of Jewish identity that has been almost completely lost today - namely, that throughout much of their history Jews were both a nation and cosmopolitan, they lived in a constant tension between particularism and universalism. And it is precisely this tension, which Sznaider seeks to capture in his innovative conception of ‘rooted cosmopolitanism', that is increasingly the destiny of all peoples today.